Visual perception during mirror gazing at one's own face in schizophrenia - Caputo, Giovanni B.; Ferrucci, Roberta; Bortolomasi, Marco; Giacopuzzi, Mario; Priori, Alberto; Zago, Stefano (Schizophrenia research, 2012)
In normal observers gazing at one's own face in the mirror for some minutes, at a low illumination level, triggers the perception of strange faces, a new perceptual illusion that has been named ‘strange-face in the mirror’. Subjects see distortions of their own faces, but often they see monsters, archetypical faces, faces of dead relatives, and of animals. We designed this study to primarily compare strange-face apparitions in response to mirror gazing in patients with schizophrenia and healthy controls. The study included 16 patients with schizophrenia and 21 healthy controls. In this paper we administered a 7 minute mirror gazing test (MGT). Before the mirror gazing session, all subjects underwent assessment with the Cardiff Anomalous Perception Scale (CAPS). When the 7minute MGT ended, the experimenter assessed patients and controls with a specifically designed questionnaire and interviewed them, asking them to describe strange-face perceptions. Apparitions of strange-faces in the mirror were significantly more intense in schizophrenic patients than in controls. All the following variables were higher in patients than in healthy controls: frequency (p<.005) and cumulative duration of apparitions (p<.009), number and types of strange-faces (p<.002), self-evaluation scores on Likert-type scales of apparition strength (p<.03) and of reality of apparitions (p<.001). In schizophrenic patients, these Likert-type scales showed correlations (p<.05) with CAPS total scores. These results suggest that the increase of strange-face apparitions in schizophrenia can be produced by ego dysfunction, by body dysmorphic disorder and by misattribution of self-agency. MGT may help in completing the standard assessment of patients with schizophrenia, independently of hallucinatory psychopathology.